2016
DOI: 10.1158/1078-0432.ccr-15-2071
|View full text |Cite
|
Sign up to set email alerts
|

PRAME as an Independent Biomarker for Metastasis in Uveal Melanoma

Abstract: Purpose Uveal melanoma (UM) can be classified by gene expression profiling (GEP) into Class 1 (low metastatic risk) and Class 2 (high metastatic risk), the latter being strongly associated with mutational inactivation of the tumor suppressor BAP1. Nevertheless, a small percentage of Class 1 tumors give rise to metastatic disease. The purpose of this study was to identify biomarkers of metastasis in Class 1 tumors. Experimental Design 389 consecutive patients with UM were assigned to Class 1 or 2 using a pros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
212
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(218 citation statements)
references
References 34 publications
5
212
1
Order By: Relevance
“…A low expression of PRAME correlated with a better 5-year OS probability, a finding similar to that observed in other cancers. (33,36,39,40) Moreover, the correlation between better OS and low PRAME expression was detected in patients belonging to SHH-and G3-MB subgroups, while a larger number of patients is needed to confirm this finding in WNT-and G4-MB subgroups. The statistically significant correlation between low PRAME expression and better OS probability was also maintained considering as cut-off for PRAME mRNA expression median value, as well as 1° and 3° quartiles.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A low expression of PRAME correlated with a better 5-year OS probability, a finding similar to that observed in other cancers. (33,36,39,40) Moreover, the correlation between better OS and low PRAME expression was detected in patients belonging to SHH-and G3-MB subgroups, while a larger number of patients is needed to confirm this finding in WNT-and G4-MB subgroups. The statistically significant correlation between low PRAME expression and better OS probability was also maintained considering as cut-off for PRAME mRNA expression median value, as well as 1° and 3° quartiles.…”
Section: Discussionmentioning
confidence: 90%
“…(29) Several authors reported PRAME expression in many cancers, but presently the biological and clinical meaning of this finding is not yet completely elucidated and, in some cases, the association between PRAME expression and disease prognosis is controversial. (30)(31)(32) In particular, in solid malignancies, including head and neck cancer, (33,34) liposarcoma,(35) uveal melanoma, (12,36) osteosarcoma, (37,38) breast cancer (39) and neuroblastoma (40) high PRAME expression correlates with advanced stage disease and poor clinical outcome, whereas in pediatric acute leukemia PRAME overexpression was found to predict good outcome. (41,42) Research.…”
Section: Discussionmentioning
confidence: 99%
“…These findings derived from primary uveal tumors have allowed us to identify a gene expression profile that is highly accurate for identifying patients at increased risk for metastatic disease [45,46]. The development of a clinically practical platform for analyzing gene expression profiles would benefit those patients at high risk for metastatic disease by strengthening surveillance efforts, permitting earlier treatment, and facilitating the enrollment of suitable patients into ongoing clinical trials [45].…”
Section: Pathogenesismentioning
confidence: 99%
“…7 NY-ESO-1 is expressed heterogeneously in SS, with only 56% of tumors expressing the antigen in more than 50% of the tumor cells. 11 PRAME-TCR engineered T-cells could be used for the treatment of other cancers as well, including medulloblastoma, since many tumor types express PRAME 8 10 , 12 14 . PRAME-TCR engineered T-cells are currently used for the treatment of refractory or relapsed acute myeloid leukemia (AML) in a phase I TCR-gene therapy trial (ClinicalTrials.gov NCT02743611).…”
Section: Discussionmentioning
confidence: 99%